1996
DOI: 10.1128/jcm.34.8.2051-2051.1996
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Gram stain to detect Propionibacterium acnes in specimens from clinically significant infections

Abstract: We have read with interest the article by Johnson et al. (7) about the variability of the results of Gram staining encountered with some anaerobes. Gram stain is one of the cornerstones for bacterial identification, but it also serves as a useful technique for rapid detection of organisms in clinical samples (6). Propionibacterium acnes is a non-spore-forming, pleomorphic, anaerobic gram-positive rod (3) that is frequently considered to be a contaminant in clinical samples but may also be implicated as the age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…In this case, P. acnes was not detected in urine via Gram staining. This was also demonstrated in a previous study [ 11 ], and should be taken into account when considering P. acnes infection as a differential.…”
Section: Discussionsupporting
confidence: 80%
“…In this case, P. acnes was not detected in urine via Gram staining. This was also demonstrated in a previous study [ 11 ], and should be taken into account when considering P. acnes infection as a differential.…”
Section: Discussionsupporting
confidence: 80%
“…has been associated with delayed diagnosis and inappropriate antibiotic therapy (7,20). All of the anaerobic gram-positive organisms in this study were characteristically decolorized (5,12) during the traditional Gram stain procedure. Using a modified Gram stain to study the staining reaction by electron microscopy, Beveridge (2) demonstrated that cytoplasmic voids were formed close to the cell wall and septation sites in P. acnes, causing the cells to lyse and appear gram negative.…”
Section: Discussionmentioning
confidence: 65%
“…This type of strategy will lead to the creation of an image database and the development of a software using machine learning, allowing for the automatic identification of the objects observed. In the long term, this would replace the technical and microbiological knowledge necessary to be able to identify the bacteria with the commonly-used staining methods such as Gram and other dyes used for microorganisms [13,30]. A major part of the cost for our method comes from the purchase of a TM4000 Plus SEM (50 k EUR).…”
Section: Discussionmentioning
confidence: 99%
“…However, Gram staining results are not always reliable due to multiple factors, such as inter-operator variability, false staining for some species, etc. [11][12][13]. Within the last decade, insufficient identifications were switched to culture and eventually relied on other high accuracy methods for microbe identification in blood cultures such as matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI TOF/MS) [14], molecular biology [15][16][17], multiplex PCR assays, specific hybridization assays, or microarrays [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%